Rising land commodification in sub-Saharan Africa: Reconciling the diverse narratives - Jayne, Thomas; Chamberlin, Jordan; Holden, Stein Terje; Ghebru, Hosaena; Ricker-Gilbert, Jacob; Place, Frank (Elsevier, 2021)
Scholarship on African land markets has proliferated in recent years. We contend that this scholarship consists of distinct literatures that examine non-overlapping parts of the system and diverge in their conclusions. Some studies view rising land markets as providing greater options for smallholder farmers and positive impacts on agricultural productivity and equity, while others emphasize large-scale land acquisitions and disenfranchisement as the dominant narrative. This article reviews these disparate literatures, identifies points of convergence and disagreement, and outlines steps required to achieve greater consensus on the effects of rising commodification of land. We conclude that land prices are rapidly rising throughout the region, that smallholder participation in land rental and purchase markets are generally rising, and that increased land market activity is generating complex distributional effects that remain poorly understood.